Application of manure and compost to contaminated soils and its effect on zinc accumulation by Solanum nigrum inoculated with arbuscular mycorrhizal fungi - Marques, Ana P. G. C. (2010)
Zn accumulation in Solanum nigrum grown in naturally contaminated soil in the presence of different types of organic amendments was assessed. Under the same conditions, the response of the plant to inoculation with two different isolates of arbuscular mycorrhizal fungi (AMF) (Glomus claroideum and Glomus intraradices) was also evaluated. S. nigrum grown in the non-amended soil always presented higher Zn accumulation in the tissues, with the addition of amendments inducing reductions of up to 80 and 40%, for manure and compost, respectively, and enhancing plant biomass yields. The establishment of S. nigrum in the Zn contaminated soil combined with the application of amendments led to a 70-80% reduction in the amount of Zn leached through the soil. The use of S. nigrum in combination with manure appeared as an effective method for reducing the effects of soil contamination, diminishing Zn transfer to other environmental compartments via percolation.